TOURISM AREA LIFE CYCLE (TALC) SEBAGAI STRATEGI PENGEMBANGAN DESA WISATA BERKELANJUTAN DI KABUPATEN BADUNG-BALI - Darsana, I Made; Suwita Yanti, Ayu; Rena Mariani, Ni Wayan (Penerbit Lafadz Jaya, 2025)
Village-based tourism has become a sustainable development strategy that contributes to the well-being of local communities through the optimization of natural and cultural potential. Tourist villages in Bali, particularly in Badung Regency, possess significant potential to be developed as attractive tourism destinations due to their cultural characteristics and natural beauty. However, without proper planning, uncontrolled tourism growth may lead to risks such as over-tourism, environmental degradation, and economic imbalance. This study employs the Tourism Area Life Cycle (TALC) approach as an analytical framework for planning the development of tourist villages in Badung, Bali. TALC allows for the identification of the stages of tourism destination development, enabling the implementation of tailored strategies to promote sustainable growth. This study adopts a descriptive qualitative method, utilizing data collection techniques such as in-depth interviews, observations, and literature reviews. The findings indicate that tourist villages in Badung are currently in the involvement stage, where local communities are beginning to actively develop basic tourism facilities but still face various challenges related to sustainability. To prevent stagnation or decline, sustainability-based strategies are necessary, including the implementation of green business practices, strict environmental regulations, and the diversification of tourism products that actively involve local community participation.